Ecological Marketing - Fonseca Saldaña, Ricardo Rolando (2019)
Marketing specialists know that in a globalized world what defines is the added value of the product. This premise is not only of technical knowledge but it is also set on the mind of the consumers: they know that the services or the products are not enough; they want something else, they look for a differentiating factor and if they find it, they reward it. Consumers are in the search of a plus or benefit for their family and social group, responsible marketing meets these expectations and emerges as one of the aspects of RSE. To reuse containers and packaging three special characteristics are stipulated. One, industrial transportation, as for example the use of pallets. Two: in repairing, reconditioning and reutilizing products, the idea is recuperating the product and making it available for sale; the objective of recycling is the use of remnants as an alternative to raw materials, which is considered responsibility of the marketing of products, and three. The strategies of transformation of materials as for instance the conversion into energy and the compost.